Intermediaries in International Conflict. - Princen, Thomas (Princeton legacy library., 2014)
Few scholars have attempted to evaluate critically the role mediators play in managing international conflicts. Thomas Princen examines where mediation fits in the larger realm of diplomatic practice, going beyond the usual state-centric focus to account for the mediating activities of a wide range of actors-from superpowers to small states, from international organizations to nongovernmental groups. Originally published in 1995. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distingui.